2018
DOI: 10.32828/mdj.v6i4.476
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apically extruded debris by using hand and rotary Nickel-Titanium instruments

Abstract: This study evaluated the amount of apical debris, using hand, rotary ProTaper instruments, and rotary ProFile instruments. Forty five of mandibular premolars with single root were randomly divided into three groups. The teeth in all groups were instrumented until reaching the working length, with ProFile, rotary ProTaper and hand PrpTaper instruments. Debris extruded from the apical foramen was collected into preweighed polyethylene vials and the extruded irrigant was evaporated. The weight of the dry extruded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The resultsare presented in table (3)(4)(5)(6)(7)(8)(9)(10)(11).showed that the Simulated mean values were higher than Dentsply and study groups. Statistical comparisons among the groups were performed using one way ANOVA test among groups revealed a statistically significant difference (P<0.05).…”
Section: Ptnmentioning
confidence: 97%
See 2 more Smart Citations
“…The resultsare presented in table (3)(4)(5)(6)(7)(8)(9)(10)(11).showed that the Simulated mean values were higher than Dentsply and study groups. Statistical comparisons among the groups were performed using one way ANOVA test among groups revealed a statistically significant difference (P<0.05).…”
Section: Ptnmentioning
confidence: 97%
“…Collecting vials were carried with tissue forceps throughout the entire experiment to prevent adhesion of any materials to the outer surface of the vial (tissue forceps was used as vial carrier). All instrumentations were done by single operator [11]. For standardization purposes, the irrigation protocol was done using a total volume of 7-mL of normal saline including a final flush of 3-mL.…”
Section: Preparation Of Canalsmentioning
confidence: 99%
See 1 more Smart Citation